Geometry of the Comptonization Region of MAXI J1348−630 through Type-C Quasiperiodic Oscillations with NICER - Kevin Alabarta; Mariano Méndez; Federico García; Diego Altamirano; Yuexin Zhang; Liang Zhang; David M. Russell; Ole König (The Astrophysical Journal)
We use the rms and lag spectra of the type-C quasiperiodic oscillation (QPO) to study the properties of the Comptonization region (aka corona) during the low/hard and hard-intermediate states of the main outburst and reflare of MAXI J1348−630. We simultaneously fit the time-averaged energy spectrum of the source and the fractional rms and phase-lag spectra of the QPO with the time-dependent Comptonization model VKOMPTH. The data can be explained by two physically connected coronae interacting with the accretion disk via a feedback loop of X-ray photons. The best-fitting model consists of a corona of ∼10 ^3 km located at the inner edge of the disk and a second corona of ∼10 ^4 km horizontally extended and covering the inner parts of the accretion disk. The properties of both coronae during the reflare are similar to those during the low/hard state of the main outburst, reinforcing the idea that both the outburst and the reflare are driven by the same physical mechanisms. We combine our results for the type-C QPO with those from previous work focused on the study of type-A and type-B QPOs with the same model to study the evolution of the geometry of the corona through the whole outburst, including the reflare of MAXI J1348−630. Finally, we show that the sudden increase in the phase-lag frequency spectrum and the sharp drop in the coherence function previously observed in MAXI J1348−630 are due to the type-C QPO during the decay of the outburst and can be explained in terms of the geometry of the coronae.